Pengaruh Service Quality dan Store environment Terhadap Impulse Buying Melalui Positive Emotion Pada Sociolla - Dhyah Harjanti; Teddy Gotama Gunawan (.Universitas PGRI Adi Buana, 2023)
This research was conducted with the aim of knowing the effect of service quality and shop environment impulsively through positive emotions on Sociolla. This type of research is quantitative research with a sample of 119 respondents. Data processing techniques and data analysis in this study used SmartPLS 4.0 software. The results of this study indicate that the store environment has an effect on positive emotions, service quality has no effect on impulse buying, service quality does not affect positive emotions, the store environment does not affect impulse purchases, positive emotions do not affect impulse purchases, positive emotions do not mediate the effect of service quality. on impulse buying, positive emotions do not mediate the influence of the store environment on impulse buying.